Parallels between subaqueous ridges on Earth and Mars: a new morphological potential indicator for paleolake assessment - Williams, Rebecca M. E.; Irwin, Rossman P.; Berman, Daniel C.; Hill, Jonathon (Frontiers in Astronomy and Space Sciences, 2025)
Water levels in large lakes fluctuate in response to climatic cycles. Surface observations from rovers have validated past lakes on Mars, following multiple studies that inventoried candidate paleolake sites across the planet in satellite observations. Attempts to identify martian paleolake highstands, a key metric for constructing lake hydrographs, are hampered by few morphological indicators of water level discernible in orbital data. Construction of paleolake hydrographs, particularly in post-Noachian sites with preserved sedimentary deposits, holds tremendous promise for elucidating climate evolution on Mars. We examined image and elevation data at three topographic basins with established or candidate paleolakes. Drawing upon a terrestrial analog, we demonstrate that some depositional paleochannel ridges on Mars may have formed subaqueously in lakes. This new insight paves the way for future studies to use this landform in detailed lake hydrograph reconstructions.